1993
DOI: 10.3146/i0095-3679-20-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Fosthiazate against Meloidogyne arenaria, Frankliniella spp., and Sclerotium rolfsii in peanut1

Abstract: The efficacy of fosthiazate, a new organophosphorus compound, against the peanut root-knot nematode (Meloidogyne arenaria (Neal) Chitwood), thrips (Frankliniella spp.), and southern stem rot (Sclerotium rolfsii Sacc.) in peanut (Arachis hypogaea L.) was studied for 2 years at Tifton, Georgia. Different rates and methods of applying granular and emulsifiable concentrate formulations of fosthiazate were compared with rates and methods of applying granular fenamiphos and aldicarb which were included as standard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The efficacy of fosthiazate in controlling pests on tomato (M. incognita), potato (Agriotes spp., Globodera pallida, and G. rostochiensis), peanuts (M. arenaria and Frankliniella spp. ), banana (Cosmopolites sordidus, Meloidogyne spp., Hoplolaimus seinhorsti, Helicotylenchus multicinctus, and Radopholus similis), and tobacco (M. javanica, M. arenaria, and M. incognita) has been evaluated in various studies and consistently confirmed its high efficiency as well as its key role in pest control (Minton et al, 1993;Rich et al, 1994;Grove et al, 2000;Chabrier et al, 2002;Saad et al, 2011).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The efficacy of fosthiazate in controlling pests on tomato (M. incognita), potato (Agriotes spp., Globodera pallida, and G. rostochiensis), peanuts (M. arenaria and Frankliniella spp. ), banana (Cosmopolites sordidus, Meloidogyne spp., Hoplolaimus seinhorsti, Helicotylenchus multicinctus, and Radopholus similis), and tobacco (M. javanica, M. arenaria, and M. incognita) has been evaluated in various studies and consistently confirmed its high efficiency as well as its key role in pest control (Minton et al, 1993;Rich et al, 1994;Grove et al, 2000;Chabrier et al, 2002;Saad et al, 2011).…”
mentioning
confidence: 92%
“…The cysts of SCN can generally survive in the soil for 3-4 years, and eggs of H. glycines cyst may remain viable for up to 11 years (Inagaki and Tsutsumi, 1971). As a soil borne pathogen, SCN can be harmful for soybean during the whole growth period; the infected soybean plants show stunting and yellowing aboveground (Niblack et al, 2006). SCN caused approximately 90 billion tons of losses for the top 10 soybean-producing countries (USA, China, Brazil, Argentina, Indonesia, Canada, India, Paraguay, Italy, and Bolivia) in 1998, and the total yield losses caused by SCN in these countries were higher than those caused by any other disease (Wrather et al, 2001).…”
mentioning
confidence: 99%
“…Fosthiazate has been widely used to control root-knot nematodes on various types of crops, including cotton, potato, peanuts and tobacco (Kimpinski et al, 1997;Lawrence and McLean, 1995;Minton et al, 1993;Rich et al, 1994;Woods et al, 1999) in the regions of Europe, Asia, and Latin America (Toki and Imai, 1994). Previous studies have suggested that the half-lives (t 1/2 ) of fosthiazate in three soils (without sterilization) ranged between 17.7 and 46.8 days in 20 C laboratory conditions, and that the low values of the Freundlich adsorption coefficients (K f ) ranged between 0.1 and 1.2 mL g À1 in three contrasting soils (Qin et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Control of the fungus is difficult as it does not produce asexual spores and overwinters as sclerotia, the primary inocula for the following season, on plant debris and in soil (Punja, 1988). Various methods of control have been investigated including genetic control (Branch and Csinos, 1987; Smith et al., 1989; Brenneman et al., 1990; Besler et al., 1997), chemical control (Hagan et al., 1988; Bowen et al., 1992; Culbreath et al., 1992; Minton et al., 1993; Brenneman et al., 1994; Damicone and Jackson, 1994; Culbreath et al., 1995), cultural practices (Gurkin and Jenkins, 1985; Punja et al., 1986) and biological control (Henis et al., 1983; Elad et al., 1984; Latunde‐Dada, 1993; Benhamou and Chet, 1996), particularly with Trichoderma and Gliocladium species (Papavizas and Lewis, 1989; Papavizas and Collins, 1990; Ristaino et al., 1991).…”
Section: Introductionmentioning
confidence: 99%